The Buffalo Nickel - Morrison, Taylor (Boston, Mass. : Houghton Mifflin, 2002)
A biography of the sculptor of the buffalo nickel, who grew up in the Dakota Territory where Sioux children were his playmates, buffalo robes were his blankets, and the town whittler was his art teacher.
"Walter Lorraine books"--P. facing t.p.
Includes bibliographical references (p. 31).
Keywords: Fraser, James Earle, -- Juvenile literature; Fraser, James Earle; Sculptors -- Biography -- United States; Coin design -- Juvenile literature. -- United States; Mints -- Juvenile literature. -- United States; Nickel (Coin) -- Juvenile literature; Sculptors; Coins; Money